Multidimensionality of inner speech and its relationship with abnormal perceptions (2016)
Background Inner speech is a common human experience. Recently, there have been studies linking this experience with cognitive functions, such as problem solving, reading, writing, autobiographical memory, and some disorders, such as anxiety and depression. In addition, inner speech is recognised as the main source of auditory hallucinations. Objectives The main purpose of this study is to establish the factor structure of Varieties of Inner Speech Questionnaire (VISQ) in a sample of the Colombian population. Furthermore, it aims at establishing a link between VISQ and abnormal perceptions. Method This was a cross-sectional study in which 232 college students were assessed using the VISQ and the Cardiff Anomalous Perceptions Scale (CAPS). Results Through an exploratory factor analysis, a structure of three factors was found: Other Voices in the Internal Speech, Condensed Inner speech, and Dialogical/Evaluative Inner speech, all of them with acceptable levels of reliability. Gender differences were found in the second and third factor, with higher averages for women. Positive correlations were found among the three VISQ and the two CAPS factors: Multimodal Perceptual Alterations and Experiences Associated with the Temporal Lobe. Conclusions The results are consistent with previous findings linking the factors of inner speech with the propensity to auditory hallucination, a phenomenon widely associated with temporal lobe abnormalities. The hallucinations associated with other perceptual systems, however, are still weakly explained. © 2016 Asociación Colombiana de Psiquiatría